Palladium nanoparticle functionalized graphene nanosheets for Li–O2 batteries: enhanced performance by tailoring the morphology of the discharge product1. Issue 90 (1st October 2015) - Wang, Liang Jun; Zhang, Jian; Zhao, Xiao; Xu, Lei Lei; Lyu, Zhi Yang; Lai, Min; Chen, Wei
<x xml:space="preserve">Abstract</x> The Li–O2 battery with palladium functionalized graphene nanosheets cathode exhibits enhanced discharge capacity and improved ORR/OER performance through tailoring the morphology of discharge product.